2022
DOI: 10.1097/nna.0000000000001126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Leader Series

Abstract: OBJECTIVEA virtual mental well-being initiative was developed for nurse leaders to provide education about mental health and to teach self-care skills.BACKGROUNDBecause of substantial demand placed on nurse leaders during the COVID-19 pandemic, organizations must address stress and burnout by providing a continuum of care to include education, support, and intervention.METHODSAll levels of nurse leaders at a multicampus healthcare system were invited to attend. Data were collected on coping, empowerment, burno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Both bottom-up and top-down commitment is needed. Sawyer et al., ( Sawyer et al., 2022 ) USA Evaluation of an initiative to enable nurse leaders to gain knowledge and skills related to well-being and self-care that may benefit their teams and themselves. 500 Nurse leaders.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both bottom-up and top-down commitment is needed. Sawyer et al., ( Sawyer et al., 2022 ) USA Evaluation of an initiative to enable nurse leaders to gain knowledge and skills related to well-being and self-care that may benefit their teams and themselves. 500 Nurse leaders.…”
Section: Resultsmentioning
confidence: 99%
“…Included studies were from USA (n=9), Italy (n=2), UK (n=2), Australia (n=2), Taiwan (n=2), Jordan (n=1), Spain (n=1), Iran (n=1), and China (n=1). 17 of the included studies were conducted in acute hospital settings or services: with 6 focusing on broad health districts ( Blake et al., 2020 , 2021 ; Holton et al., 2022 ; Olcoń et al., 2022 ; Sawyer et al., 2022 ; Sawyer et al., 2022 ), 5 focusing on single or multiple hospital sites ( Castillo-Sánchez et al., 2022 , Carter and Turner, 2021 , Hsieh et al., 2022 , Muir et al., 2022 , Zaghini et al., 2021 )) and 6 focusing on individual units or wards, including a range of specialty areas such as Intensive Care Units ( Drexler et al., 2023 , Green et al., 2022 ), Emergency ( Haugland et al., 2023 , Yang et al., 2022 ), Surgical ( King et al., 2022 ), and COVID-19 care wards ( Nourian et al., 2021 ). One study conducted by Chen et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen studies focused on different burnout interventions (Akugue, 2022; Azizoddin et al, 2021; Blake et al, 2020; Crippa et al, 2021; Cunningham et al, 2017; Dincer & Inangil, 2021; Ferreres‐Galán et al, 2022; Giordano et al, 2022; Horn et al, 2019; Hsieh et al, 2022; Miyoshi et al, 2022; Sawyer et al, 2022; Sijbrandij et al, 2020; Sis Çelik & Kılınç, 2022). Of these studies, 13 assessed the effectiveness of an intervention, and one reported the development and usability of an intervention (Blake et al, 2020).…”
Section: Resultsmentioning
confidence: 99%